Examining certain blood parameters of sporters of national boxing team before and after the match - Pala, Ragıp (My University, 2013)
Research group of this study consists of total 10 boxers who are actively involved in Turkish big male national boxing team and with average age of 22.40 age/years. Blood samples were taken twice from boxers constituting the research group before and after the match after the camp program of eight weeks applied for research group. Data and laboratory results are utilized as covariant. Relative changes in the data obtained are analyzed by SAS package program and by utilizing PROC MEANS procedure. Significance level of changes observed is specified by Paired t test that adds significance at the level of P<0.05. Statistically significant increase is observed in the glucose levels of boxers as one of the blood parameters before and after the match (P=0.0014). Decrease in the insulin levels is determined before and after the match, however it is not found statistically significant (P=0.1059). It is observed that cortisol levels have increased before and after the match, however it is not considered statistically meaningful (P=0.0534). Decrease in the urea levels is determined before and after the match, however the difference is not found statistically significant. (P=0.5837). Differences in the creatine levels before and after the match are found to be insignificant (P=0.0815). According to the results of the research, important changes in all blood parameters of sporters of national boxing team are observed before and after the match, however statistically significant difference is observed only in glucose parameter. Thus, it can be stated that our application caused significant changes only in the glucose parameter among the parameters we examined.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Boxer; Exercise; Glucose; Match; Blood